Probiotics Modulate Mouse Gut Microbiota and Influence Intestinal Immune and Serotonergic Gene Expression in a Site-Specific Fashion - Taverniti, Valentina; Cesari, Valentina; Gargari, Giorgio; Rossi, Umberto; Biddau, Cristina; Lecchi, Cristina; Fiore, Walter; Arioli, Stefania; Toschi, Ivan; Guglielmetti, Simone (Frontiers in Microbiology, 2021)
Probiotic microorganisms may benefit host by influencing diverse physiological processes, whose nature and underlying mechanisms are still largely unexplored. Animal models are unique tool to understand the complexity of the interactions between probiotic microorganisms, the intestinal microbiota and the host. In this regard, in this pilot study, we compared the effects of 5 days-administration of three different probiotic bacterial strains (Bifidobacterium bifidum MIMBb23sg, Lactobacillus helveticus MIMLh5, and Lacticaseibacillus paracasei DG) on three distinct murine intestinal sites (ileum, cecum and colon). All probiotics preferentially colonized cecum and colon. In addition, probiotics reduced in the ileum and increased in the cecum and colon the relative abundance of numerous bacterial taxonomic units. MIMBb23sg and DG increased in the ileum the inducible nitric oxide synthase (iNOS), which is involved in epithelial homeostasis. In addition, MIMBb23sg upregulated the cytokine IL-10 in the ileum and downregulated the cyclooxygenase COX-2 in the colon, suggesting an anti-inflammatory/regulatory activity. MIMBb23sg significantly affected the expression of the main gene involved in serotonin synthesis (TPH1) and the gene coding for the serotonin reuptake protein (SERT) in the ileum and colon, suggesting a potential propulsive effect toward the distal part of the gut, whereas the impact of MIMLh5 and DG on serotonergic genes suggested an effect towards a motility control. The three probiotics decreased the expression of the permeability marker zonulin in gut distal sites. This preliminary in vivo study demonstrated the safety of the tested probiotic strains and their common ability to modulate the intestinal microbiota. The probiotics affected host gene expression in a strain-specific manner. Notably, the observed effects in the gut were site dependent. This study provides a rationale for investigating the effects of probiotics on the serotonergic system, which is a topic still widely unexplored.